Arms Control and Disarmament Agreements, 1959-1972 - ARMS CONTROL AND DISARMAMENT AGENCY WASHINGTON DC (1972)
Includes the full texts of arms control and disarmament treaties between the United States and other parties from 1959-1972. Includes the Antarctic Treaty, the "Hot Line" Agreement, Limited Test Ban Treaty, Outer Space Treaty, Treaty for the Prohibition of Nuclear Weapons in Latin America, Non-proliferation Treaty, Seabed Arms Control Treaty, Accidents Agreement, "Hot Line" Modernization Agreement, Biological Weapons Convention, SALT ABM Treaty, SALT Interim Agreement.